Molecular And Antibody Based Diagnosis Of Bovine Viral Diarrhea Virus (Bvdv) Associated With Cattle From Mathura, Uttar Pradesh (India) (Applied Biological Research, 2012)
Bovine viral diarrhea (BVD) infection causing great  reproductive and productive losses is an immunosuppression  seen in all age groups of ruminants world-wide. In present study  out of 78 peripheral blood leucocyte (PBLs) samples 4 samples  were positive for BVDV antigen by pestivirus antigen-capture  ELISA, while none of the faecal samples was positive for BVDV  antigen by AGID and RT-PCR. The use of RT-PCR on all  PBLs samples was restricted to the above 4 positive samples  which yielded a 288 bp amplicon, while rest were found  negative. The BVDV positive samples were confirmed by restriction endonuclease analysis. The study revealed the presence of BVDV in Mathura region of Uttar Pradesh.
Keywords: BVDV; RT-PCR; PBL’s; ELISA